Penerapan Pembelajaran Problem Based Learning untuk Meningkatkan Ketrampilan Berpikir Kritis Siswa Pada Mata Pelajaran PPKn - I Made Kartika; Putu Ronny Angga Mahendra; Viane Awa (Universitas Pendidikan Ganesha, 2020)
The problem at SMK Dwijendra Denpasar in PPKn is that students are less active in critical thinking and less active in expressing opinions. The success in PPKn learning lies in the use of the learning model. The problem-based learning model has specifications that can train students to actively think critically in solving problems, and dare to express opinions. The purpose of this research is to determine the application of problem-based learning models to improve students 'critical thinking skills in PPKn subjects and to find out the obstacles in applying problem- based learning models to improve students' critical thinking skills in PPKn subjects. This research uses descriptive qualitative method. The research location is at SMK Dwijendra Denpasar. Observation data collection techniques, and documentation. Data analysis was performed using an interactive data analysis model that was carried out through the process of data reduction, data presentation, and drawing conclusions / verification. The results of the study showed that the application of problem-based learning model based on problems to improve students' critical thinking skills in Pancasila and civics education subjects had been implemented in accordance with the learning implementation plan. The application of problem-based learning models to improve students 'critical thinking skills improves students' critical thinking skills, increases student learning activities, and increases responsibility attitudes. Obstacles in the application of the based learning model are less learning time, less education to be a good facilitator at the group guidance stage, and to students who are less active in group discussions. The suggestion that can be given is that the school needs to conduct socialization so that it is more optimal for the application of problem-based learning models, for teachers to be more able to increase creativity in the use of learning models, to be more efficient in the time available during the teaching and learning process, as well as during the learning process. actively guiding students in group discussions.